Milices et guérillas paysannes face à l’armée régulière: le combat asymétrique au Rio de la Plata et la fragmentation territoriale (1810-1852) - Alejandro M. Rabinovich (Amnis)
This paper analyzes the Spanish-American civil conflicts from the first half of the 19th century through the lens of their usually asymmetric nature, where permanent forces of the central governments were facing militias of provinces and regions. The article briefly explores some theoretical bases available to consider the relationship between the outcome of these clashes and the territorial settings established in each space. Then, from a case study on the Río de la Plata region, it discusses the type of military cohesion generated by the various fighting forces and, consequently, the tactical capabilities to achieve victory at battle. Thus this work contributes to an explanation of the predominance of local militia forces and the territorial fragmentation experienced by the region.